Evaluate P(x) = x4 + 3x2 + 2 by substituting any value for x that has not been used already in this discussion.

May be this one will help you.

P(x) = x^{4} +3x^{2} + 2

Let's substitute x^{2} by z (it can be any letter)

z = x^{2}

Then

P(z) = z^{2} + 3z + 2 = (z + 1)(z + 2). In the term of x, given function will be

**P(x) = (x ^{2} + 1)(x^{2} + 2)** That's all we can do in the set of real numbers

P(x) = (x -

**i**)(x +

**i**)(x -

**i**√2)(x +

**i**√2) - in the set of complex numbers (

**i**

^{2}= -1)

## Comments

Bob -

"in this discussion" - Is there more information that you can add to this problem?

None that I am aware of. Substitution of polynominal expressions, that's all that is asked.

Bob